OBYWATELSTWO TZW PÓŹNYCH PRZESIEDLEŃCÓW1 NIEMIECKICH. ROZWAŻANIA NA TLE PRAWA MIĘDZYNARODOWEGO (CZĘŚĆ II) - Muszyński, Mariusz (Wydział Prawa i Administracji UAM, 2005)
Citizenship is a legal tie that connects a person to a certain state. Although, as a rule, decisions regarding citizenship lie within the exclusive competence of the state, one can observe an increasing role of the international law in that matter, and consequently a limitation of sovereign rights of the state which is now forced to take into account the will of the person in question in matters related to the granting, changing or depriving of citizenship. The only one, exceptionally accepted possibility, is a collective regulation of citizenship in the case of a territorial succession. This was the case regarding Polish-German relations after the acquisition by Poland in 1945 of parts of the former Third Reich, and the consequent international obligations arising from Potsdam-Yalta regulations which called for displacement of German citizens beyond the new borders. In the year 2005, already 60 years after the 2nd World War, the issue of citizenship of persons who had left for Germany after 1945, came back as an off-shot of the property-reparations dispute and has now constituted a certain political problem. The paper is a legal analysis of the post-war national verification pursued within the territories attached to Poland as a consequence of the Potsdam displacement decisions as well as the later deprivations of Polish citizenship exercised on those who, between 1945 and 1989, had left Poland to live in either of the two German States. It is indicated , against the background of the post-first-world-war solutions regarding national questions (Versailles standard), that this problem should be looked at from the point of view of Potsdam regulations. In the paper, an assessment of the national regulations is pursued in the light of international law. It covers an analysis of the official legislation of the Polish People’s Republic (1945-1989), the unpublished international and national acts and the quasi-precedent judiciary of the Polish courts. Its aim is an attempt to answer the question of the factual status of the said persons in the Polish law today. The conclusion of the analysis indicates that the international and national legal acts are in conflict as there are certain legislation gaps and political misconceptions of successive Polish governments, including the present one. Further, it is proved that from the legal point of view, the current Polish foreign politics according to which the issue of the German „displaced” citizenship constitutes „Poland’s internal problem” is wrong and disadvantageous. The solution should rather lead to force Germany to regulate the issue on the basis of international agreements in the real interests of Poland i.e. the confirmation of the deprivation of their Polish citizenship of those „displaced”. Keeping the current status quo may result in a verification of Potsdam regulations and will be a victory of the German policy seeking of the revision of the obligations and penalties for the aggression and the war.
CITIZENSHIP OF THE ‘LATE DISPLACED GERMANS’. CONSIDERATIONS OF THE ISSUE IN THE LIGHT OF THE INTERNATIONAL LAW